2002
DOI: 10.1103/physrevd.65.084009
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of the central singularity in spherical collapse

Abstract: We analyze here the structure of non-radial nonspacelike geodesics terminating in the past at a naked singularity formed as the end state of inhomogeneous dust collapse. The spectrum of outgoing nonspacelike null geodesics is examined analytically. The local and global visibility of the singularity is also examined by integrating numerically the null geodesics equations. The possible implications of existence of such families towards the appearance of the star in late stages of gravitational collapse are consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…We conclude this by showing that at the most, along one singular geodesic the redshift remains finite, while along all other (infinite family of) singular geodesics the redshift diverges. Earlier Deshingkar et al [6] had shown a similar result for the Tolman-Bondi-Lemaître (TBL) dust model. For the null singularities, this gives a strong evidence in support of CCC, as even though geodesics come out from the singularity we will not be able to see them as no energy or information will reach an observer from such a singularity.…”
supporting
confidence: 59%
See 4 more Smart Citations
“…We conclude this by showing that at the most, along one singular geodesic the redshift remains finite, while along all other (infinite family of) singular geodesics the redshift diverges. Earlier Deshingkar et al [6] had shown a similar result for the Tolman-Bondi-Lemaître (TBL) dust model. For the null singularities, this gives a strong evidence in support of CCC, as even though geodesics come out from the singularity we will not be able to see them as no energy or information will reach an observer from such a singularity.…”
supporting
confidence: 59%
“…(9) we see that along the larger root w(r) does not go to zero as r goes to zero and there is only one geodesic coming out of this direction. While along smaller root w(r) = De that at the central singularity K t remains finite along the larger root and it blows up as a negative exponential power of r along the smaller root direction [6]. This exponential divergence is not very surprising as these geodesic stay very close to apparent horizon near the center.…”
mentioning
confidence: 92%
See 3 more Smart Citations